Socialism of fools : capitalism and modern anti-Semitism - Battini, M. (Michele) (Columbia University Press, 2016)
Michele Battini focuses on the critical moment during the enlightenment in which anti-Jewish stereotypes morphed into a sophisticated, modern social anti-Semitism. He recovers the potent anti-Jewish, anticapitalist propaganda that cemented the idea of a Jewish conspiracy in the European mind and connects it to the atrocities that characterised the Jewish experience in the 19th and 20th centuries.